Hispanic amphorae along Illyria and Epirus. Preliminary report - Ribera , Albert; De Mitri , Carlo (Rei Cretariae Romanae Fautorum Acta, 2024)
The presence of western goods and containers, often attested by only a few units, indicates that this area was part of the trade networks that linked the western and eastern Mediterranean. Notably, the Ionian-Adriatic basin was a major market for Hispanic products throughout the Roman period. Roman amphorae – mostly Greco-Italic and Lamb. 2 types from Adriatic Italy – began arriving to the region in the Hellenistic period. During this early period, Iberian productions were rare, chiefly Punic-Ibizan vessels found from Montenegro (Risan) to Albania (Skhodar, Orikos) and in the Greek Epirus. From the 1st century AD, Roman Hispanic amphorae, especially Baetican Dr. 7-11, 12, 20 and Haltern 70 types, become common in land and maritime Dalmatian sites. This is less the case in southern Dalmatia, but we think that these differences in distribution are more the result of the poor excavation methodologies in certain sites than a reflection of historical reality. This paper aims at reviewing finds of Hispanic vessels in the region.